Border and Cultural heritage - Approaches to a complex topic - Dum-Tragut, Jasmine (History and Culture, 2025)
In the following, some thoughts on the concepts of border, cultural heritage and territoriality are presented to illustrate the complex intertwining of these three concepts. And hence, the handling the protection of cultural heritage in border areas, especially in newly established border areas and post-war territorial changes, shall also be briefly discussed on the de iure well-established “theoretical” instruments of international laws and conventions in contrast to the often de facto arbitrary national practise of sovereign states.
Keywords: border settlement; conflict; convention; cultural heritage; international law